Model Project Based Learning Berbasis Deep Learning dalam Mengembangkan Kemampuan Berpikir Kreatif Anak Usia Dini: Kajian Literatur - Ratnaningsih, Hanifa Ayu; Ningrum, Mallevi Agustin; Malaikosa, Yes Matheos Lasarus; Fitri, Ruqoyyah; Kristanto, Andi; Adhe, Kartika Rinakit (UNIB Press, 2026)
Early childhood education must be designed meaningfully and child-centered to foster creative thinking as a fundamental 21st-century competency. Creative thinking in early childhood is reflected in children’s capacity to generate diverse, flexible, and original ideas, as well as to develop concepts grounded in their learning experiences. The Project Based Learning (PjBL) model is considered relevant for nurturing this competency, as it engages children actively in learning through contextual, project-based activities. When integrated with the Deep Learning approach, instruction extends beyond activity completion to encompass meaning-making, experiential reflection, and purposeful understanding of learning objectives. This study aims to analyze and synthesize findings from prior research on the implementation of the Project Based Learning model integrated with Deep Learning in developing creative thinking ability in early childhood. A qualitative approach employing a literature review method was applied, examining 20 peer-reviewed articles published between 2020 and 2025. The findings reveal that Project Based Learning encourages children to develop ideational fluency, cognitive flexibility, and simple problem-solving skills through meaningful learning experiences. The Deep Learning approach strengthens children’s cognitive processes by emphasizing comprehension, reflection, and the connection between learning experiences and generated ideas. The integration of both approaches has been shown to create learning environments that are not oriented toward a single correct answer, but instead accommodate the diversity of children’s thinking.